Protectors of the Great Victory: Commemoration of World War II in the Russian Community of Toronto - Rogova, Anastasia (Anthropologica, 2022)
Political mobilization of the Russian-speaking immigrant community in Canada is a relatively recent phenomenon, but it has permeated multiple spheres of community life in recent years. This paper examines how Russian- speaking immigrants living in the Greater Toronto Area (GTA) used the history and memory of World War II to mobilize their community from 2014–21, what forms of war commemoration they performed, and what these commemoration practices meant for the community and the individuals who participated in them. The commemorative practices and performances in the GTA’s Russian-speaking community remained controversial as they borrowed extensively from Soviet and post-Soviet political imagery and rituals, yet, as I argue in this article, political activism of Russian-speaking immigrants was also informed by Canadian multiculturalism policies and international political discourses and was intimately linked to their demands for full citizenship and cultivation of their identities in Canadian society.